(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In the earlier times inIndia, the law would give protection only from physical dangers such astrespass from which the Right to Property emerged to secure his house andcattle. This was considered to be part of Right to Life. As the ever changingcommon law grew to accommodate the problems faced by the people, it wasrealized that not only was physical security required, but also security of thespiritual self as well as of his feelings and intellect was required. Thestrategy adopted by the Supreme Court with a view to expand the ambit of Art.21 and to imply certain right there from, has been to interpret Art.21 alongwith international charters on Human Rights. Right to privacy is not enumeratedas a Fundamental Right in the Constitution of India. In the context of Article19(1) (d), the right to privacy was again considered by the Supreme Court in1975. In the context of surveillance, it has been held that surveillance, ifintrusive and seriously encroaches on the privacy of citizen, can infringe thefreedom of movement, guaranteed by Article 19(1) (d) and Article 21.Surveillance must be to prevent crime and on the basis of material provided inthe history sheet.